A Genotypic Comparison Reveals That the Improvement in Nitrogen Remobilization Efficiency in Oilseed Rape Leaves Is Related to Specific Patterns of Senescence-Associated Protease Activities and Phytohormones - Poret, Marine; Chandrasekar, Balakumaran; van der Hoorn, Renier A. L.; Déchaumet, Sylvain; Bouchereau, Alain; Kim, Tae-Hwan; Lee, Bok-Rye; Macquart, Flavien; Hara-Nishimura, Ikuko; Avice, Jean-Christophe (Frontiers in Plant Science, 2019)
Oilseed rape (Brassica napus L.) is an oleoproteaginous crop characterized by low N use efficiency (NUE) that is mainly related to a weak Nitrogen Remobilization Efficiency (NRE) during the sequential leaf senescence of the vegetative stages. Based on the hypothesis that proteolysis efficiency is crucial for the improvement of leafNRE, our objective was to characterize key senescence-associated proteolytic mechanisms of two genotypes (Ténor and Samouraï) previously identified with contrasting NREs. To reach this goal, biochemical changes, protease activities and phytohormone patterns were studied in mature leaves undergoing senescence in two genotypes with contrasting NRE cultivated in a greenhouse under limiting or ample nitrate supply. The genotype with the higher NRE (Ténor) possessed enhanced senescence processes in response to nitrate limitation, and this led to greater degradation of soluble proteins compared to the other genotype (Samouraï). This efficient proteolysis is associated with (i) an increase in serine and cysteine protease activities and (ii) the appearance of new cysteine protease activities (RD21-like, SAG12-like, RD19-like, cathepsin-B, XBCP3-like and aleurain-like proteases) during senescence induced by N limitation. Compared to Samouraï, Ténor has a higher hormonal ratio ([salicylic acid] + [abscisic acid]) / ([cytokinins]) that promotes senescence, particularly under low N conditions, and this is correlated with the stronger protein degradation and serine/cysteine protease activities observed during senescence.